Maternal Mortality: In-Depth Review of Maternal Death in a Referral Hospital in Jigawa State Nigeria - Abdullahi Habib; Zaro Boysungni; Abubakar Shehu; Usain Ahmad; Mumini Rasheed (West African Journal of Allied Health Sciences, 2026)
Background: Maternal mortality remains a major public health challenge in Nigeria. In 2023, Nigeria accounted for approximately 28.5% of global maternal deaths despite representing only 2.6% of the world’s population. This study aims to determine the maternal mortality ratio (MMR) and identify factors contributing to maternal deaths at Rasheed Shekoni Federal University Teaching Hospital (RSFUTH), Dutse. Methods: A retrospective review of maternal deaths that occurred in the Department of Obstetrics and Gynaecology, RSFUTH, between 1 December 2023 and 30 November 2024 was conducted. Relevant information was extracted from patients’ case files using a structured proforma. Data were analyzed using IBM SPSS version 26. Descriptive statistics were presented as frequencies and percentages, while associations were tested using Fisher’s exact test at a significance level of p